Freedom and Neighbourhood: Reflecting on the Example of Fred Dewey - Kasper, Rafael; Dewey, Fred; Heuer, Wolfgang; Spaid, Sue; Paquay, JF; Petropoulos, Renée; Petropoulos-White, Pilar; Kohn, Jerome; Gaynor, Fergal; Mahrdt, Helgard (HannahArendt.net, 2023)
Content Private and Public Memories of Fred Dewey Rafael Kasper General Public - A Fable of Sanctuary Fred Dewey General Public – Eine Fabel von einem (un-)geschützen Ort Fred Dewey Fred und wir Wolfgang Heuer Fred and us Wolfgang Heuer Memories Sue Spaid Erinnerungen Sue Spaid Memories JF Paquay Memories Renée Petropoulos The Twelve Mortal Men Pilar Petropoulos-White Hannah Arendt on Being Human and Political Power Jerome Kohn ‘Touch With Your Hands His Things’ Fergal Gaynor In memoriam Fred Dewey Helgard Mahrdt